Nocturnal dipping of heart rate and blood pressure in people with HIV in Tanzania. Issue 7 (2nd June 2021) - Nolan, Cody; Reis, Karl; Fadhil, Salama; Etyang, Anthony; Ezeomah, Chiomah; Kingery, Justin R.; Desderius, Bernard; Lee, Myung‐Hee; Kapiga, Saidi; Peck, Robert N.
Abstract: People with HIV (PWH) have a >2‐fold greater risk for development of cardiovascular disease (CVD), which may be associated with abnormalities in 24‐h ambulatory blood pressure measurement (ABPM) profile. We conducted a nested case‐control study of ABPM in 137 PWH and HIV‐uninfected controls with normal and high clinic blood pressure (BP) in Tanzania. Nocturnal non‐dipping of heart rate (HR) was significantly more common among PWH than HIV‐uninfected controls ( p = .01). Nocturnal non‐dipping of BP was significantly more common in PWH with normal clinic BP ( p = .048). Clinical correlates of nocturnal non‐dipping were similar in PWH and HIV‐uninfected adults and included higher BMI, higher CD4 + cell count, and high C‐reactive protein for HR and markers of renal disease for BP. In conclusion, nocturnal non‐dipping of both BP and HR was more common in PWH but further research is needed to determine causes and consequences of this difference.